Problem Penentuan Karier Alumni Prodi Bimbingan Penyuluhan Islam Fakultas Dakwah Dan Komunikasi Islam UIN-SU Medan - Zulkarnain Abdurrahman; Mutiawati Mutiawati; Misrah Misrah (Journal on Education, 2024)
The success of an institution that produces graduates is seen from the extent to which the graduates are able to practice knowledge in their field in society. This is in line with the learning objective, namely so that students can be useful and useful in contributing their knowledge according to their field of expertise. The phenomenon that occurs today is that there are still many undergraduate graduates who work in areas that do not match their major. Ideally, someone can pursue a career and profession that suits their major while studying. This was revealed from the results of interviews with several alumni of the Islamic Counseling Guidance department that there are still many alumni who work in ways that do not match the department they are pursuing. Some work in banks, PLN, Samsat, teachers and school operators. This of course can cause concern among department students because alumni are a barometer and example of success in determining a career. The objectives of this research are: (1) To find out the factors that influence alumni of the BPI department to choose careers that are not in accordance with their field of expertise, (2) To find out the efforts made by the BPI department in responding to the problem of determining their alumni's careers. The research method used is research qualitative. The research subjects for the FGD consisted of 24 people, namely alumni of the BPI Department whose careers were not in accordance with their department's competencies and the research subjects for the interview were 2 people, namely Ka. BPI Study Program and Secretary. The research data were analyzed using descriptive analysis. The results of the research show that there are two factors faced by BPI alumni who experience a mismatch in their career with the field of expertise they studied during their studies: (1) Internal factors, namely factors that reside within the alumni, such as a lack of interest and mastery of major competencies as well as a lack of effort to find information about the world of work, (2) External Factors, namely factors related to things that come from outside the alumni themselves, including family factors, lack of job opportunities appropriate to the major, salary problems and the lack of guidance and career services while on campus.